THE ROLE OF THE SOCIAL ECONOMY IN SUSTAINABLE DEVELOPMENT: AN ANALYSIS OF COOPERATIVES - VĂDUVA CONSTANTIN-DANIEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This paper explores the significance of the social economy in promoting sustainable development. By examining cooperatives and social enterprises, this study highlights how organizations prioritizing social objectives over profit contribute to economic resilience, social inclusion, and environmental sustainability. This research employs a qualitative methodology, using case studies and empirical evidence to underline the contributions of the social economy to equitable economic growth. The findings suggest that supporting the social economy can foster more inclusive and sustainable development models, which have gained prominence amidst global economic, social, and environmental challenges.